2013
DOI: 10.1177/1470320313497818
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone enhances the beneficial effect of aliskiren on cardiac structural and electrical remodeling in TGR(mRen2)27 rats

Abstract: Objective: To investigate the influence of simultaneous administration of spironolactone (20 mg/kg per day, intraperitoneal (i.p.)) and aliskiren (50 mg/kg per day, i.p.) for a period of eight weeks on cardiac remodeling in TGR(mRen2)27 rats. Methods: Echocardiographic and electrophysiological and histological methods were used to determine the influence of spironolactone and aliskiren on cardiac remodeling. Results: 1) the beneficial effect of aliskiren on SBP was enhanced by simultaneous administration of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Recent observations indicated that spironolactone enhances the beneficial effect of aliskiren on cardiac structural and electrical remodeling in TGR(mRen2)27 rats (122) and that chronic administration of eplerenone to the failing heart reduces the cardiac effect of Ang II on inward calcium current through a decline in AT1 receptor level at the surface cell membrane (91). Because AT1 receptor is a mechanosensor involved in cardiac remodeling, it is reasonable to think that part of the beneficial effect of spironolactone in the failing heart is related to a smaller sensitivity of cardiac muscle to mechanical stress.…”
Section: On the Role Of Aldosterone And Mineralocorticoid Receptorsmentioning
confidence: 99%
“…Recent observations indicated that spironolactone enhances the beneficial effect of aliskiren on cardiac structural and electrical remodeling in TGR(mRen2)27 rats (122) and that chronic administration of eplerenone to the failing heart reduces the cardiac effect of Ang II on inward calcium current through a decline in AT1 receptor level at the surface cell membrane (91). Because AT1 receptor is a mechanosensor involved in cardiac remodeling, it is reasonable to think that part of the beneficial effect of spironolactone in the failing heart is related to a smaller sensitivity of cardiac muscle to mechanical stress.…”
Section: On the Role Of Aldosterone And Mineralocorticoid Receptorsmentioning
confidence: 99%
“…Furthermore, it reduces ventricular mass according to the ALLAY study, which revealed that ALI is as effective as losartan in the reduction of hypertrophied ventricular mass in hypertensive patients with BMI >25 kg/m 2 (Solomon et al, 2009). Myocardial thickness was reduced, according to many articles that analyzed the effects of ALI (Table 1) in cardiac experimental models (Campbell et al, 2011;De Mello, 2015;Fischer et al, 2008;Takamura et al, 2016;Weng et al, 2014;Yamada et al, 2016).…”
Section: Many Randomized Control Trials Have Shown Significant Resultsmentioning
confidence: 99%